Experimental Investigation of radiative proton-capture reactions relevant to Nucleosynthesis - Khaliel, A.; Mertzimekis, T. J.; Psaltis, A.; Psyrra, I.; Kanellakopoulos, A.; Lagaki, V.; Foteinou, V.; Axiotis, M.; Harrisopulos, S. (HNPS Advances in Nuclear Physics, 2019)
One of the primary objectives of the field of Nuclear Astrophysics is the study of the elemental and isotopic abundances in our solar system. Although a lot of progress has been made regarding a large number of nuclides, there is still a number of neutron-deficient nuclei, ie the p nuclei, which cannot be created via the s and r processes. These processes are responsible for the production of the bulk of heavy nuclides. The pre-explosive or explosive phases of massive stars are considered potential loci for p nuclides production via various combinations of photodisintegrations and nucleon captures, along with β+ decays and electron captures. For the study of the vast network of nuclear reactions (over 20’000) that are responsible for observed isotopic abundances, the statistical model of Hauser-Feshbach is employed. The model requires the knowledge of nuclear reaction cross sections, quantities that can be measured in the laboratory. In this work, we report on recent experimental attempts to measure such cross sections in radiative proton-capture reactions involving 107,109Ag near the astrophysically relevant energy window. Measurements have been performed at the Tandem Accelerator Laboratory of the N.S.C.R. “Demokritos”. The results are compared to various theoretical models, using the TALYS and EMPIRE codes, in an attempt to provide experimental input to astrophysical models.